Analysis of Purchasing Power Parity: Empirical evidence between Mexico and the United States - Gómez Aguirre, Mario; Rodríguez Chávez, José Carlos (Estudios Económicos de El Colegio de México, 2012)
This paper analyzes evidence on Purchasing Power Parity between Mexico and the United States, as well as the causal link between relative prices and exchange rate (1957-2010). We use a unit root test that allows for two structural changes and two tests of causality. The results indicate that the PPP between Mexico and the United States is validated, reflecting the integration and price convergence of the two economies to a very rapid rate. In addition, the exchange rate follows the behavior of relative prices of both countries.